Analysis of calculation methods used for accuracy evaluation of the results of road accident examination - Nagurnas, Saulius; Mickūnaitis, Valentinas; Pečeliūnas, Robertas; Vestartas, Aurelijus (Transport, 2008)
For examination of road accidents often calculations are being performed according to mathematical equations having many variables, real values of which are of stochastic nature and they depend on many accident factors. Therefore it is important to know limits of determination of final values of every being analysed parameter of car movement and their probabilistic characteristics. This paper presents some cases of simulation of some road situations by mathematical methods of calculations, which now are widely used for evaluation of accuracy of values of the calculated parameter (in this paper ‐ the braking distance). Also here is presented some analysis of these methods. The paper presents the following cases of car braking: braking with making attempts to prevent a collision with another car, braking through impact‐to‐pedestrian prevention and conventional (rectilinear) car braking. The main attention in the analysis of the mentioned road situations is paid to veracity of the car braking distance, i.e. to limits of variation of values of this parameter and also to influence of accidental factors on the final result which is being looked for. Some conclusions on the expediency of application of the described methods of calculations to analysis of road accidents are present. First published online: 27 Oct 2010